Of men and monsters : Jeffrey Dahmer and the construction of the serial killer - Tithecott, Richard (The University of Wisconsin Press, 1997)
Of Men and Monsters examines the serial killer as an American cultural icon, one that both attracts and repels. Richard Tithecott suggests that the stories we tell and the images we conjure of serial killers - real and fictional - reveal as much about mainstream culture and its values, desires, and anxieties as they do about the killers themselves. Why, for example, does Hannibal Lecter, though clearly dangerous, seem brilliant, even alluring, while his dark counterpart in Silence of the Lambs, Buffalo Bill, represents pure monstrosity? In a nation where murders occur every day, why do those we name "serial killers" seem so different, meriting a flood of public and media attention?